Personality styles in patients with psoriasis - Martín Brufau, Ramón; Corbalán Berná, Javier; Brufau Redondo, Carmen; Ramirez Andreo, Antonio; Limiñana Gras, Rosa María (Anales de Psicología / Annals of Psychology, 2010)
The relationship between skin diseases and psychological factors has been well documented in scientific literature. Among the skin diseases with clear psychological component is the psoriasis. The correla-tion between the worsening of skin lesions and increased levels of psy-chopathology in response to stressful events has been described previously in this disease. However, studies comparing personality in psoriasis and normal population using objective tests have been limited and not conclu-sive. Purpose: To determine whether any variable of personality styles involved in the development or maintenance of psoriasis disease. Method: We compared a sample of 36 psoriasis patients with normal (non dermatological disease) population. Results: Psoriasis patients showed differences in motivational goals, cogni-tive and interpersonal behavior characteristic modes and a lower setting rate than the normal population. Conclusions: This study presents data supporting the existence of a person-ality profile different from the normal population and that could act as a risk factor for the onset and / or maintenance of psoriasis.